Perkembangan Berbahasa Indonesia Di Kalangan Masyarakat Sekarang (International Forum of Researchers and Lecturers, 2024)
An arbitrary system of sound symbols that its members use to cooperate, communicate, and identify themselves is language. Language allows humans to express thoughts, concepts, ideas, and desires by communicating opinions and information. Language in daily life began to change and was replaced by the use of adolescent language known as slang. Slang continues to become more common due to advanced developments and easy access to different types of information. Therefore, this research was carried out through literature research to obtain a comprehensive understanding of the development of the Indonesian language. These data were analyzed using qualitative techniques. The national language of Indonesia was established in 1928 and reclassified as a national language in 1945. Indonesian is a cultural product, a tool for social efforts, and a language of communication. Indonesian is used in a variety of life situations. Indonesian is a national language that unites people from various social, cultural, and linguistic backgrounds. The role of the Indonesian language is the last communication tool that prioritizes national interests over the interests of regions, tribes, and groups. and communicate meaning effectively to the interlocutor. The good and correct use of Indonesian is based on general guidelines to improve Indonesian spelling. The development of the Indonesian language is very important for the future of society because it helps people understand concepts, opinions and feelings and plays a role as the national language of communication and information exchange.